Transactional Mentorship: A Flourishing Mentor-Mentee Relationship in Bioethics - Senghor, Abdou (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2024)
This text proposes a transactional mentoring perspective to help bioethics students better address the ethical challenges that exist in all areas of social life. A transactional approach is best suited to bioethics mentoring that produces positive change and fosters human flourishing on the part of both mentor and mentee.